Where do we stand with immune checkpoint blockade for advanced cutaneous squamous cell carcinoma? A systematic review and critical appraisal of existing evidence - Steeb, Theresa; Wessely, A.; Heppt, Franz; Harlaß, M.; Berking, Carola; Heppt, Markus (British Journal of Dermatology, 2020)
Immune checkpoint blockade (ICB) has tremendously changed the field of oncological therapy. Recently, the PD-1-blocking antibody cemiplimab was approved by the FDA and the EMA for the treatment of advanced cutaneous squamous cell carcinoma (cSCC).1 However, clinical practice guidelines currently do not cover specific recommendations regarding the management of advanced cSCC with ICB. Hence, we have performed a systematic review on the current use of ICB for advanced cSCC.
EVALuna2:212852